Global Standards and Social Contracts: The Political Economy of Bibliographic Description - Campbell, Grant D. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper compares information description in library cataloguing, the Semantic Web and the Web 2.0. It relates them to three separate but related principles in classical political economy: Thomas Hobbes’s state of nature, Jean-Jacques Rousseau’s social contract, and Adam Smith’s invisible hand. Cette communication compare la description de l’information dans les catalogues bibliographiques, le Web sémantique et le Web 2.0. Ces pratiques sont mis en relief avec trois principes distincts, mais connexes de l’économie politique classique : l’état de la nature de Thomas Hobbes, le contrat social de Jean-Jacques Rousseau et la main invisible d’Adam Smith.